Congestion Management Solution for Hybrid System Considering Voltage Stability Margin. (2016) - Sagwal, Rahul; Kumar, Ashwani
Abstract: In deregulated structure, power system network has become more complex with free trades amongst GENCOs and DISCOs and with increasing penetration of Renewable Energy Sources. These complexities might impose risk on security and stability of the network especially during congestion hours. This paper presents an economical and secure congestion management approach, in hybrid power system; by considering linear piece-wise hydro model and probabilistic wind generation model. Impact of wind participation in congestion management and bidding's effect on congestion cost has been analyzed. Minimization of congestion cost has been formed as major objective and problem has been formulated as Mixed Integer Non Linear Programming (MINLP) problem which has been tested on modified IEEE-24 bus RTS system. Locational dependence of congestion cost and a comparison of VSM based approach with conventional congestion management approach have also been presented.